The Addiction of Electronic Sport (E-Sport) among UUM Undergraduate Students - Hamzan, Muhammad (Universiti Utara Malaysia, 2020)
Electronic sport (E-sport) is a competitive playing of computer games and video games in a multi-player mode. This can be found either on the internet or locally during a large organized event that has been giving positive effects recently. However, addiction to E- sport could bring negative effects to study performance and health. This addiction gives a bad result for the students’ life. The purpose of this study is to analyze the effect of E-sport addiction among undergraduate students at Universiti Utara Malaysia (UUM). By using the qualitative research method, the data were collected from 5 undergraduate students at UUM through face to face interviews. Analyzing the data, the study found the effects of E-sport addiction on study performance and health. This study provides valuable information that can contribute to the body of knowledge related to E-sport and may serve as a reference for future research.